Data conversion from ARC/INFO format into MGE INTERGAPH, for INTERGRAPH HELLAS - Skarlatos, Dimitrios (My University, 2026)
Data conversion from ARC/INFO format into MGE INTERGAPH, for INTERGRAPH HELLAS